СОСТОЯНИЕ ИССЛЕДОВАНИЯ РОЛИ ХИМИЧЕСКИХ ЭЛЕМЕНТОВ В АГРОХИМИИ И ЭКОЛОГИИ - Ибрагимов, Б.А.; Авезов, Б. (SCIENCE and SOCIETY, 2024)
The article discusses triple irradiation of a sample using instrumental neuroactivation analysis of soils. The calculation of the content of the determined elements was carried out using a specially developed computer program.